Coupling of NURBS and Meshfree RPIM for plane stress of web with openings. (May 2022) - Mokhtaram, M.H.; Noor, M.A. Mohd; Nazir, M.Z. Jamil Abd; Abidin, A.R. Zainal; Yassin, A.Y. Mohd
Abstract: This study presents a novel approach for the coupling of the non-uniform rational B-spline (NURBS) with the radial basis functions (RBF) under the framework of the meshfree radial point interpolation method (RPIM). In this method, denoted as N-RPIM, the NURBS basis functions are employed to model the geometry of the problem domain exactly, whilst the RPIM is used for field variables interpolation. The formulation is applied to the web of a cellular beam under plane stress condition to highlight the advantages. The results show that the method works efficiently, and provides favourable performance against FEM. The solution of the former converges faster, thus highlighting the potential of N-RPIM for future development.